Using Bloom’s taxonomy to teach course content and improve social media literacy - Callens, Melissa Vosen (Journal of Interdisciplinary Studies in Education, 2019)
Social media can engage students in active learning opportunities and be used to teach almost any course concept. In addition to teaching course concepts, using social media in a classroom can help students critically think about a technology they use multiple times a day. While some instructors may shy away from using these tools, intimidated by the digital natives registered for their courses, they should not. Even though most students use social media regularly, many do not know how to use it professionally. This article will outline activities that incorporate social media and can be used in any classroom. The activities correspond with each level of Bloom’s revised taxonomy of the cognitive domain; using this taxonomy allows instructors to introduce social media slowly and push students toward higher-level thinking.